Turbo Warrants under Hybrid Stochastic and Local Volatility. (18th December 2013) - Lee, Min-Ku; Yoon, Ji-Hun; Kim, Jeong-Hoon; Cho, Sun-Hwa
Abstract : This paper considers the pricing of turbo warrants under a hybrid stochastic and local volatility model. The model consists of the constant elasticity of variance model incorporated by a fast fluctuating Ornstein-Uhlenbeck process for stochastic volatility. The sensitive structure of the turbo warrant price is revealed by asymptotic analysis and numerical computation based on the observation that the elasticity of variance controls leverage effects and plays an important role in characterizing various phases of volatile markets.